2015
DOI: 10.1021/acsami.5b04504
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Oxide Nanoparticles and Iridium/Iridium Oxide Nanocomposites: Photochemical Fabrication and Application in Catalytic Reduction of 4-Nitrophenol

Abstract: Hydrous iridium oxide (IrOx) nanoparticles (NPs) with an average diameter of 1.7 ± 0.3 nm were prepared via photochemical hydrolysis of iridium chloride in alkaline medium at room temperature. The photoinduced hydrolysis was monitored by time-dependent ultraviolet-visible (UV-vis) spectroscopy, and the effects of the incident wavelength and irradiation time on the production of IrOx NPs were systematically investigated. It was found that UV-vis irradiation is crucial for the generation of IrOx NPs during the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 73 publications
6
82
1
Order By: Relevance
“…As the amount of NaBH 4 substantially exceeds that of 4‐NP in the system, the reaction can be treated as a pseudo‐first‐order reaction with respect to the concentration of 4‐NP . Thus the kinetics information can be obtained according to Equations (1)–(3): -dc/dt=kappc ln(c/c0)=-kappt -kapp/m=K …”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…As the amount of NaBH 4 substantially exceeds that of 4‐NP in the system, the reaction can be treated as a pseudo‐first‐order reaction with respect to the concentration of 4‐NP . Thus the kinetics information can be obtained according to Equations (1)–(3): -dc/dt=kappc ln(c/c0)=-kappt -kapp/m=K …”
Section: Figuresupporting
confidence: 93%
“…As a result of their high specific surface area and strong adsorption ability, numerous nanomaterials have been used to catalyze the reduction of 4‐NP. These can be classified into three main categories, namely, noble metals (Ag, Au, Pt, Pd, Ir, etc. ), non‐noble metals (Cu, Mn, etc.…”
Section: Figurementioning
confidence: 99%
“…For solution C (prepared from IrCl 3 ), clear peaks at 327 and 390 nm and a small peak at 550 nm were observed, and as expected the overall absorbance of this solution was much lower than the solutions prepared from H 2 IrCl 6 [22,23]. In this case, the peak at 390 nm is assigned to Ir(H 2 O) 3 Cl 3 [18], and the peak at 327 nm is assigned to the hydrolysis product [Ir(OH) 6 ] 3- [24]. Interestingly, others have suggested that ageing the precursor solution prior to use can greatly improve the deposition process [7,10,16], so it is worthwhile to note that the aged IrCl 3 solution reported elsewhere [10] 2-peaks and the development of a spectra similar to the initial IrCl 3 solution ( Figure 1b).…”
Section: Influence Of the Iridium Precursor Solutionsupporting
confidence: 57%
“…that between 550 and 800 nm) increased considerably during the deposition process, most likely due to the formation of IrO x nanoparticles within the solution (which exhibit a broad absorption peak around 570-580 nm [21,24,26]). In some cases, a faint blue precipitate was observed in solution B after deposition which is likely to be IrO x .…”
Section: Influence Of the Iridium Precursor Solutionmentioning
confidence: 99%
See 1 more Smart Citation